2000
DOI: 10.1038/sj.bjp.0703428
|View full text |Cite
|
Sign up to set email alerts
|

The emetic and anti‐emetic effects of the capsaicin analogue resiniferatoxin in Suncus murinus, the house musk shrew

Abstract: 1 In Suncus murinus the ultrapotent capsaicin analogue resiniferatoxin (RTX) induced an emetic response in the dose range 1 ± 1000 mg kg 71 , s.c. The latency was inversely related to dose and ranged from 41.2+4.4 min. (1 mg kg 71 , .).3 RTX (100 mg kg 71 , s.c.) induced c-fos-like immunoreactivity in the area postrema and parts of the nucleus tractus solitarius. This pattern is consistent with the proposal that the emetic e ect is mediated via one or both of these structures and an involvement of substance P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 36 publications
(66 reference statements)
3
58
1
Order By: Relevance
“…Furthermore, we have verified our results using a specific nonpeptide NK-1R antagonist, L703,606. Previous studies have indicated that such nonpeptide NK-1R antagonists can cross the blood-brain barrier and exert central effects (27)(28)(29). We demonstrate that systemic administration of this agent significantly inhibits N. meningitidis and B. burgdorferi-induced CNS gliosis, demyelination, and associated inflammatory cytokine elevations while attenuating concomitant decreases in IL-10 levels.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, we have verified our results using a specific nonpeptide NK-1R antagonist, L703,606. Previous studies have indicated that such nonpeptide NK-1R antagonists can cross the blood-brain barrier and exert central effects (27)(28)(29). We demonstrate that systemic administration of this agent significantly inhibits N. meningitidis and B. burgdorferi-induced CNS gliosis, demyelination, and associated inflammatory cytokine elevations while attenuating concomitant decreases in IL-10 levels.…”
Section: Discussionmentioning
confidence: 63%
“…The most typically employed antiemetic treatments are those that act as antagonists of the serotonin subtype-3 (5-HT 3 ) receptor. Indeed, 5-HT 3 antagonists also suppress vomiting in a variety of species, including cats (Rudd et al 2000), ferrets (Ozaki and Sukamoto 1999) and shrews (Torii et al 1991;Ito et al 1995;Andrews et al 1996Andrews et al , 2000Matsuki et al 1997;Darmani 1998). In human clinical trials, although 5-HT 3 antagonists are effective in treating the acute phase of chemotherapy-induced emesis, considerable evidence indicates that the 5-HT 3 antagonists are relatively ineffective in attenuating the delayed phase of chemotherapy induced emesis (Fabi et al 2003) as well as anticipatory nausea and vomiting upon reexposure to the cues associated with treatment (Tyc et al 1997;Morrow et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown in S. murinus that while serotonin was emetic, it could also induce an anti-emetic effect on motion sickness and that this was possibly due to a desensitization of the emetic pathway or activation of a different sites or pathways [23]. Furthermore, studies by Andrews et al [42] revealed that while resiniferatoxin was emetic, it also had an anti-emetic effect to emesis induced by nicotine, cisplatin, motion and copper sulphate in S. murinus, possibly via depletion of the neurotransmitter substance P [42].…”
mentioning
confidence: 99%